2021
DOI: 10.1097/inf.0000000000003353
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Parapneumonic Effusion/Pleural Empyema in Japan

Abstract: Background: Pediatric parapneumonic effusion/ pleural empyema (PPE/PE) is a severe infectious condition, and its management should be guided by local epidemiology and the patient's medical history. This survey aimed to determine the clinical and bacteriologic features of PPE/PE in Japan. Methods: A nationwide retrospective questionnaire survey was conducted, targeting 159 pediatric specialist training medical facilities for inpatients ≤18 years of age who were admitted for PPE/PE between January 2007 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…While PPEs can usually be treated with antibiotics without chest tube drainage; in case of empyema, a chest tube should be inserted and pus drained and intrapleural fibrinolytic therapy should be used if necessary. 4,6,8,13 Imaging methods and laboratory findings can be used to differentiate empyema from PPE. In an adult study conducted from Turkey in the empyema group, WBC, CRP, ALC, and LMR were found to be significantly higher than PPE group and LMR was more sensitive than other markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While PPEs can usually be treated with antibiotics without chest tube drainage; in case of empyema, a chest tube should be inserted and pus drained and intrapleural fibrinolytic therapy should be used if necessary. 4,6,8,13 Imaging methods and laboratory findings can be used to differentiate empyema from PPE. In an adult study conducted from Turkey in the empyema group, WBC, CRP, ALC, and LMR were found to be significantly higher than PPE group and LMR was more sensitive than other markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rates of pathogens causing PPE/empyema have changed with the spread of Streptococcus pneumoniae and Haemophilus influenzae type b vaccine in recent years, the most frequently detected bacterial pathogens are still S. pneumoniae, Streptococcus pyogenes, and Staphylococcus aureus. [5][6][7] Rapid differentiation of PPE and empyema in pediatric emergency departments (PED) is important in terms of managing patients and providing timely treatment, predicting prognosis and avoiding unnecessary invasive procedures. Imaging methods, acute phase reactants, and pleural fluid sampling are helpful in distinguishing PPE/ empyema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nationwide retrospective study of hospital cases of pediatric empyema over a 10-year period in Japan, the 3 major pathogens were Group A streptococci, S. pneumoniae and S. aureus 32 (Table 8).…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Several studies have reported that the most common bacterial causes of parapneumonic effusion or empyema include the Streptococcus milleri group, Streptococcus pneumoniae, and Staphylococcus aureus [ 21 ]. Many infectious microorganisms can reduce nitrate to nitrite [ 22 , 23 , 24 ], which further inspired us to hypothesize whether the nitrite concentration and/or nitrite/nitrate ratio in PEs could help with the IPE diagnosis.…”
Section: Introductionmentioning
confidence: 99%